The Application of Technological Adaptation in the Targeted School of Teaching Campus - Wantini; Siti Muthia Dinni; Cikal Jiwani Putri; Mutia Eka Putri (Universitas Pendidikan Ganesha, 2022)
Technological adaptation is being pursued, especially in the educational world, which is currently in an emergency period, thus it forces learning adaptation. During this time, human' brains start to think the new ways to solve their problems or what helps their activities. From this process, technology emerges and is growing. Technology has many benefits and convenience in the world of education, but it still has not fully benefited yet in education. Furthermore, the government created the program the Kampus Mengajar to improve the quality of schools from many sides, one of them being technology. This research aimed to design the program of technological adaptation conducted in the targeted school for the Kampus Mengajar. The research design used classroom action research. The subjects involved students of grade 5 in the targeted school for Kampus Mengajar. The data of this research were collected by observation, interviews, and documentation. The data were analyzed by qualitative descriptive analysis. The results of this finding showed that the uses of video, online quizzes, zoom meeting, computer device, the application of the AKSI assessment, and AKM simulation are effective, though it was not maximally used for online learning. This research concludes that several programs require more in-depth preparation to be effective in online learning in the targeted schools of the Kampus Mengajar.